Analisis Pengetahuan Siswa melalui Pembelajaran Penemuan di Sekolah Dasar Pahlawan - Ramdhan Witarsa; Dini Xena Dista (Jurusan PGMI FTIK IAIN Metro Lampung, 2020)
The purpose of this study is to get an overview of the knowledge of Pahlawan Elementary School students about energy change. The research method used is quantitative descriptive research method. In this research, inquiry learning is carried out on the subject of energy change. Throughout research, learning is based on inquiry learning that is linked to the environment. Overall students answer the questions given related to changes in energy and the environment. The results of what students think about these questions are analyzed and conclusions drawn. The results of this study indicate that students' knowledge in the Pahlawan Elementary School about energy change is still developing. This is indicated by several misunderstandings that occur continuously and repeatedly. The novelty of this research is the existence of a new step of inquiry learning that is different in theory in general. The implication of this research is the need to improve the ability of teachers to assist the implementation of inquiry learning, this is so that a long concept does not occur.